Doula Perspectives on Lactation Education and Breastfeeding Support for Diverse, Low-income Women: A Field Report. Issue 5 (3rd September 2022) - Louis-Jacques, Adetola F.; Deubel, Tara F.; Vereen, Shanda; Hernandez, Ivonne; Taylor, Melina; Miller, Elizabeth M.; Wilson, Ronée
ABSTRACT: Women living below the federal poverty level have low breastfeeding rates and historically have lacked access to doula care. This disparity is particularly evident among African American women. The objective of this pilot study was to assess doulas' experiences delivering lactation education to racially/ethnically diverse, primarily Medicaid-eligible pregnant women and describe doulas' perceptions of client barriers to breastfeeding. We also wanted to understand doulas' views of infant feeding and lactation education during their participation in a quality improvement intervention that trained doulas to provide lactation education and breastfeeding support at 4 clinics serving low-income clients. Two focus groups were conducted with 7 doulas. Focus group data were transcribed, coded, and analyzed using qualitative thematic analysis. Doulas reported close relationships with their clients and provided consistent breastfeeding support and education to women in prenatal, birth, and postpartum phases of care. Doulas emphasized the need for more lactation education, especially to overcome clients' perceived milk insufficiency and early termination due to breastfeeding barriers. Doula-led breastfeeding education and support may improve breastfeeding outcomes for diverse women from underserved areas.